Potential Adverse Impacts of Sea Sand Export Policy on Ecologically Sustainable Development in Indonesia - Beni, Rozi; Atsari, Sharfina Milla (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2023)
After a 20-year hiatus in sand exports, Indonesia has reinstated the practice through Republic Indonesia Government Regulation Number 26 of 2023 (GR 26/23). GR 26/23 has stirred controversy due to its perceived conflict with Ecologically Sustainable Development (ESD) and Indonesia's green constitution outlined in Articles 28H and 33 of the 1945 Constitution. In response to this relatively new regulation, this research aims to provide a focused perspective on the legal implications of GR 26/23. Previous studies have predominantly explored ecological consequences, leaving room for legal analysis. Employing normative juridical research methods, this study examines the provisions of GR 26/23 and their legal impacts on the environment. The findings indicate incongruence between the sand export provisions in GR 26/23 and the principles of the Indonesian environmental law regime. Articles 9 and 18 of GR 26/23 suggest inadvertent support for environmental exploitation. Supported by Maritime Law and the Job Creation Law, GR 26/23 exhibits relative permissiveness toward sea sand exploitation. Consequently, GR 26/23's objective in managing sea sedimentation has paradoxical effects on achieving sustainable development, as business and ecological goals are misaligned. Therefore, stemming from the Green Contract Theory, this research advocates for the implementation of environmentally friendly incentive schemes for sand export stakeholders to achieve practical policy outcomes. Thus, policymakers are encouraged to reconsider GR 26/23 provisions through the development of incentive schemes, aligning sea sand export activities with ecologically sustainable development, and promoting harmony between economic activities and environmental preservation.